Analysis of Labor Productivity Using Marvin E. Mundel’s Partial Productivity Measurement Method in Ammonia Production at PT. X - Siagian, Nabila Prita Rizqika; Safariyani, Eva; Suherman, Rizkia Lucyani (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
To maintain competitiveness and efficiency in the chemical manufacturing industry, particularly in large-scale continuous ammonia production, optimal labor management is essential. This study analyzes labor productivity in the ammonia production process at PT , specifically in the Ammonia 1A production unit, using the partial productivity measurement method. The primary objective is to measure the contribution of labor to production output and identify the factors that cause productivity fluctuations. The method employed compares ammonia output with labor input for the period of January to December 2024. In addition, downtime analysis and a fishbone diagram were utilized to evaluate the root causes of productivity decline. The results indicate significant fluctuations in labor productivity, with the highest value recorded in November (775.8 tons/person) and the lowest in September (412.79 tons/person). The decrease in productivity is attributed to labor shortages, equipment failures, and suboptimal work procedures. The average productivity index during the observation period was 97.17%, reflecting a decline compared to the base month. These findings provide a foundation for strategic recommendations to improve workforce management and enhance operational efficiency